Folic Acid Levels During Pregnancy Regulate Trophoblast Invasive Behavior and the Possible Development of Preeclampsia - Rahat, Beenish; Hamid, Abid; Bagga, Rashmi; Kaur, Jyotdeep (Frontiers in Nutrition, 2022)
Background: One of the unique features of placentation is its similarity to tumorigenesis yet being very well regulated. It allows rapid proliferation, migration, and invasion of mononuclear trophoblast cells into the maternal uterus and remodeling the maternal vasculature. This pseudomalignant nature of trophoblastic cells is strictly regulated and its importance becomes evident in abnormal pregnancies that are characterized by aberrant trophoblast proliferation/invasion like preeclampsia. In addition to this, the importance of folic acid supplementation during pregnancy is well documented. We aimed to analyze the molecular and epigenetic regulation of the pseudomalignant nature of placentation via folic acid levels. Methods: Placental tissue samples were collected from different pregnancies in three different gestational stages. We estimated the impact of folic acid levels on global methylation, LINE1 methylation, and expression of DNMTs in all three gestational stages in pregnant women and preeclampsia pregnancies. We also analyzed the effect of folic acid supplementation on trophoblastic invasion using placental derived cells viz, JEG-3 and HTR-8/SVneo cell line and verified the molecular and epigenetic mechanisms involved in this regulation. Results: Development of preeclampsia was observed to be associated with lower folate levels in placental tissue, higher global methylation level, higher expression of DNMT1and DNMT3A. Folic acid supplementation was found to increase the invasive potential of placental trophoblasts by almost two folds which were associated with the decreased expression of tumour suppressor genes and tissue inhibitors of matrix metalloproteinases; and increased expression of oncogenes, telomerase gene, and matrix metalloproteinases. These folic acid-mediated changes were observed to be regulated by CpG methylation in the case of many genes. Folic acid supplementation was also observed to significantly decrease global methylation in placental trophoblasts related to decreasing expression of DNMT1 and DNMT3A. Conclusion: Lower folic acid levels are associated with preeclampsia development and folic acid supplementation regulates the invasive potential of placental trophoblasts as mediated by various epigenetic changes in the placenta suggesting the protective effect of folic acid against preeclampsia.